An Interesting Case of a 57-Year-Old Male with an Upper Gastrointestinal Bleeding and Obstructive Uropathy with Bilateral Hydronephrosis Diagnosed with Systemic Mucormycosis - Dora E. Izaguirre-Anariba; Felicia Chee; Zeyar Thet; Jesus Lanza (Case Reports in Infectious Diseases)
Mucormycosis is a rare and invasive fungal disease with high mortality rate caused by members of the order Mucorales. Mucorales species are vasotrophic organisms that may cause angioinvasive disease in immunosuppressed hosts. Risk factors include diabetic ketoacidosis, chronic kidney disease, organ or bone marrow transplantation, neutropenia, burns, malignancies, and steroid therapy. There are six different clinical presentations of mucormycosis, which includes rhino-orbital cerebral, pulmonary, gastrointestinal, cutaneous, disseminated, and miscellaneous infection. Here, we report a case of a 57-year-old male with stage-IV sarcoidosis on long-term steroids presenting with upper gastrointestinal bleeding and obstructive uropathy who was diagnosed with systemic mucormycosis. Biopsy obtained by endoscopy revealed necrotic debris with acute leukocytic exudate and numerous variably sized, 90-degree angulated fungal hyphae favoring mucormycosis-causing species. Imaging studies showed hydronephrosis, and cystoscopy findings were consistent with fungal infection of the bladder. Isavuconazonium sulfate was used as systemic salvage therapy along with continuous bladder irrigation with amphotericin-B for localized bladder infection after a trial with first-line systemic treatment with intravenous liposomal amphotericin-B failed. A repeat endoscopy showed inflammatory changes with a pathology report in which mucormycosis was no longer appreciated. The patient was discharged home to complete 6 months of antifungal therapy with monthly follow-ups. The patient has been asymptomatic after 12-month completion of therapy.